Pengaruh Produk, Harga dan Pelayanan Terhadap Keputusan Pembelian Pada Department Store Pasaraya Sri Ratu Pemuda Semarang - Utami, Apong; Prihatini, Apriatni Endang; Listyorini, Sari (Jurnal Ilmu Administrasi Bisnis, 2014)
The purpose of this study was to determine whether there is an influence of merchandise, prices and service to the department store purchasing decisions in Pasaraya Sri Ratu Pemuda department store Semarang. The population on this research are all consumers who have ever made purchase on Pasaraya Sri Ratu Department Store Semarang. The samples are 100 responden. The sampling method using purposive sampling, data collection techniques using literature review, interviews and observation. Questionnaire test using validity and reliability test, while the hypothesis test using the t-test, F-test and the coefficient of determination. This research shows that there is a positive effect of the merchandise with the purchase decision of 0.360 (36%), prices on purchase decisions of 0.232 (23.2%), services with purchasing decisions of 0.457 (45.7%), and and taken together the variables of merchandise, prices and service influence on purchase decisions of 0,509 (50,9%).